Cost-Sharing, Physician Utilization, and Adverse Selection Among Medicare Beneficiaries with Chronic Health Conditions - Hoffman, Geoffrey (Med Care Res Rev, 2014)
Pooled data from the 2007, 2009, and 2011/12 California Health Interview Surveys were used to compare the number of self-reported annual physician visits among 36,808 Medicare beneficiaries ≥65 in insurance groups with differential cost-sharing. Adjusted for adverse selection and a set of health covariates, Medicare fee-for-service (FFS) only beneficiaries had similar physician utilization compared to HMO enrollees but fewer visits compared to those with supplemental (1.04, p=0.001) and Medicaid (1.55, p=0.003) coverage. FFS only beneficiaries in very good or excellent health had fewer visits compared to those of similar health status with supplemental (1.30, p=0.001) or Medicaid coverage (2.15, p=0.002). For sub-populations with several chronic conditions, FFS only beneficiaries also had fewer visits compared to beneficiaries with supplemental or Medicaid coverage. Observed differences in utilization may reflect efficient and necessary physician utilization among those with chronic health needs.